A Study of The Alpha – Nucleus Scattering - Sarker, DR; Huda, Ain Ul; Das, SK; Hasan, Md K; Parvej, Md M; Rahman, Md A; Gupta, HM Sen (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Angular distribution data for the elastic scattering of 1.37 GeV alpha particles from several nuclei are analyzed in terms of the three parameter strong absorption model of Frahn and Venter. The fits are quite satisfactory over practically the entire angular range and the best fit parameters are obtained. These are used for the study of the inelastic scattering of alpha particles leading to the collective states in nuclei. A reasonably good fit is obtained without any adjustment of the parameters suggesting thereby the success of the strong absorption model. Deformation parameters are extracted for the collective states in nuclei. Asiat. Soc. Bangladesh, Sci. 40(2): 249-258, December 2014